Electronically scanned arrays : MATLAB modeling and simulation - Brown, Arik D. (Arik Darnell) (CRC Press, 2012)
"[Contains] more lengthy mathematical derivations than most {comparable books]! for arrays, provides for a unique, stand-alone mathematical description that can be adopted by anyone trying to communicate the theoretical foundation for their array design!has insights from a practitioner that are unique. The MATLAB(R) scripts alone are worth the price."--Daniel C. Ross, Ph. D, Northrop Grumman Corporation Electronically Scanned Arrays: MATLAB(R) Modeling and Simulation is considered the first book to provide comprehensive modeling/simulation programs used to design and analyze Electr.